Assessing the effectiveness of targeted agents in adjuvant therapy for patients with metastatic colorectal cancer undergoing surgical resection: a retrospective cohort study - Su, Yi-Chia; Wu, Chih-Chien; Chen, Yu-Hsun; Su, Chien-Chou; Chang, Yu-Ching; Hsieh, Meng-Che; Kao Yang, Yea-Huei (Therapeutic advances in medical oncology, 2024)
Background: Primary tumor resection and metastasectomy may be beneficial for many patients with metastatic colorectal cancer (mCRC). Objective: To assess the differences in postoperative survival outcomes between adjuvant therapy with chemotherapy alone and chemotherapy plus targeted agents (TAs). Design: Retrospective cohort study. Methods: Patients with mCRC who underwent surgical resection for primary colorectal tumor and distant metastases and received adjuvant therapy from 1 January 2010 to 31 December 2017 were enrolled in the Taiwan Cancer Registry. We analyzed the overall survival of patients with resectable or initially unresectable mCRC who received adjuvant chemotherapy alone and chemotherapy plus TAs. Results: We enrolled 1124 and 542 patients with resectable and initially unresectable mCRC, respectively. Adjuvant chemotherapy plus TAs and chemotherapy alone resulted in similar mortality rates among patients with resectable mCRC [adjusted hazard ratio (aHR) = 1.13; 95% confidence interval (CI), 0.93–1.36]; however, it marginally reduced the mortality rate among patients with initially unresectable mCRC who underwent conversion surgery after neoadjuvant therapy (aHR = 0.81; 95% CI, 0.62–1.06). The subgroup analysis of patients who received more than nine cycles of TAs preoperatively and anti-epidermal growth factor receptor agents revealed aHRs of 0.48 (95% CI, 0.27–0.87) and 0.33 (95% CI, 0.18–0.60), respectively. Conclusion: Adjuvant chemotherapy plus TAs may improve survival in patients with initially unresectable tumors who underwent conversion surgery following neoadjuvant therapy with TAs, especially in those who respond well to the targeted therapy. Our study underscores the importance of stratifying patients with mCRC based on tumor resectability when selecting the adjuvant therapy regimen.